Globalization, Border Reconstruction Projects, and Transnational Crime - Wonders, Nancy A. (Social justice, 2007)
Part of a special issue on the role of criminal organizations and individuals, and that of political states and their economic partners in transnational crime. A study was conducted to examine the relationship between globalization, border reconstruction projects, and transnational crime. Data were obtained from a review of the literature on two forms of transnational crime: accommodation and accumulation. Findings revealed that the changing border constructions that have taken place due to contradictions in the political economy of global capitalism have facilitated transnational crime. Findings indicated that criminologists must pay greater attention to crimes of accumulation in particular, such as the widespread workplace exploitation of migrants by businesses and corporations. Findings suggested that criminologists must be willing to explore whether contemporary border strategies increase or decrease social harm and to challenge strategies that facilitate harm or even death. Findings are discussed in detail.